Los charrúas en la memoria nacional de Uruguay - Szilágyi Chebi Mariá Elena (Acta Hispanica, 2015)
The Charrúas were an indigenous group who lived in the territories of the former Banda Oriental (present Uruguay, the provinces of Entre Ríos, Santa Fe and Corrientes in Argentina, and Rio Grande do Sul, Brazil). Throughout the 18th century occurred campaigns of “civilization” of the governors of Buenos Aires against indigenous, resulting hundreds of deaths. In the first half of the 19th century the indigenous people, after they fought in the armies for independence of Uruguay, were persecuted and sought to exterminate systematically the Charrúas. This fact is known as “the massacre of Salsipuedes” (1831). Nowadays several organizations have been created to rebuild, investigate and clarify the facts, and assist all kinds of Charruan cultural survival. This paper attempts to present the various ways in which the Charrúas survive in the national memory of Uruguayan society at present. At the same time, the role of the Charrúas in the formation of the national identity of Uruguay is also examined.